An Integrated Systems Model for Preventing Child Sexual Abuse - Jones, A. author. aut Link
X, 273 p.
Keywords: This book sets out an integrated systems model which utilizes a public health approach and 'whole of society' philosophy for preventing and responding to child sexual abuse. It guides those engaged in policy, practice and planning concerning gender based violence and child abuse towards a more systemic approach to tackling these problems.